2012
DOI: 10.1088/2040-8978/15/2/025705
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic multi-Gaussian Schell-model beams

Abstract: A recently introduced class of scalar multi-Gaussian Schell-model (MGSM) beams is extended to the electromagnetic domain. The realizability conditions and the beam conditions for the parameters of the new source are established. The behavior of the polarization properties of the beam on propagation in free space and in first-order imaging systems is investigated. The formation of the uniform polarization state in the central part of the transverse beam cross-section is explored in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…It is found that the spectral density is Gaussian-like for p 1 < and the amplitude of the spectral density increases with the increasing of the FRFT order. Only when p 1 = , the rectangular flat-topped distribution is formed, which distinguishes the EM RGSM beam from the multi-Gaussian Schell model beam with a circular flat-topped region formed in the far field [2,4]. It is also worthy to note that the case of p 1 = corresponds to the standard Fourier transform, which theoretically consists with the conclusion in Ref.…”
Section: Numerical Analysissupporting
confidence: 59%
See 1 more Smart Citation
“…It is found that the spectral density is Gaussian-like for p 1 < and the amplitude of the spectral density increases with the increasing of the FRFT order. Only when p 1 = , the rectangular flat-topped distribution is formed, which distinguishes the EM RGSM beam from the multi-Gaussian Schell model beam with a circular flat-topped region formed in the far field [2,4]. It is also worthy to note that the case of p 1 = corresponds to the standard Fourier transform, which theoretically consists with the conclusion in Ref.…”
Section: Numerical Analysissupporting
confidence: 59%
“…The far field generated by RGSM beam propagating in free space may have flat square/rectangular intensity distribution, which is different from the flat circular intensity distribution produced by the multiGaussian Schell model beams or the electromagnetic sinc Schellmodel beams [2][3][4][5]. The pattern of the RGSM beam throughout far field keeps invariant.…”
Section: Introductionmentioning
confidence: 93%
“…[11] It will be convenient for detection of intensity statistics and polarization properties to generate electromagnetic beams with flat intensity profiles. A recently developed model for such a beam [21] gives for the elements of matrix (1) in the source plane the expressions:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The phase screens for the SLMs can be prepared with the help of a recently developed method [18] and they obey single-point Gaussian statistics with desirable two-point correlation function. For this paper, correlation functions leading to Multi-Gaussian Schell-model beams [19][20][21] have been used because of their flat far-field intensity profiles convenient for uniform field detection. The turbulence simulator is designed as a chamber with hot air flowing in two orthogonal directions and allows for potential (see also [22]) and anisotropic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a Laguerre-Gaussian correlated Schell-model (LGCSM) beam or a Bessel-Gaussian correlated Schell-model (BGCSM) beam [7] is capable of producing ring-shaped beam profile in the far field; the transverse maximum intensity of a non-uniformly correlated (NUC) beam is shifted during propagation [5]. Not only the intensity distribution, but also the polarization properties can be controlled by modulating the correlation functions [13,14].…”
Section: Introductionmentioning
confidence: 99%